Irreversible Cysteine-Selective Protein Labeling Employing Modular Electrophilic Tetrafluoroethylation Reagents - Václavík, Jiří; Zschoche, Reinhard; Klimánková, Iveta; Matoušek, Václav; Beier, Petr; Hilvert, Donald; Togni, Antonio (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Fluoroalkylation reagents based on hypervalent iodine are widely used to transfer fluoroalkyl moieties to various nucleophiles. However, the transferred groups have so far been limited to simple structural motifs. We herein report a reagent featuring a secondary amine that can be converted to amide, sulfonamide, and tertiary amine derivatives in one step. The resulting reagents bear manifold functional groups, many of which would not be compatible with the original synthetic pathway. Exploiting this structural versatility and the known high reactivity toward thiols, the new-generation reagents were used in bioconjugation with an artificial retro-aldolase, containing an exposed cysteine and a reactive catalytic lysine. Whereas commercial reagents based on maleimide and iodoacetamide labeled both sites, the iodanes exclusively modified the cysteine residue. The study thus demonstrates that modular fluoroalkylation reagents can be used as tools for cysteine-selective bioconjugation.
Keywords: cysteine; Cysteine; bioconjugation; lysin; proteiny; jod; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; fluoroalkylation; karbodiimidy; aminy; cystein; Lysine; Amines; sulfhydrylové sloučeniny; enzymes; Iodine; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Carbodiimides; fluorine; Sulfhydryl Compounds; Proteins; hypervalent iodine